PENGARUH HUMAN RELATION, KONDISI LINGKUNGAN KERJA DAN GAYA KEPEMIMPINAN TERHADAP ETOS KERJA (Studi Kasus pada Pengurus Koperasi Mahasiswa Ilham Ramadhan Universitas Islam Malang) - Achmad Wahyu Eriyanto; Hadi Sunaryo; M. Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACTThis study aims to examine and analyze the influence of human relations, working environment conditions and leadership style on the work ethic of the management of the Student Cooperative "Ilham Ramadhan"  Islamic University of Malang both partially and jointly. Population and sample were all administrators totaling 33 people. Data collection through questionnaires. Data analysis in this study using SPSS version 17. The sampling technique using questionnaire distribution method and data testing techniques used in this study include validity test, reliability test, normality test, multiple linear regression analysis, and testing the research hypothesis.The results of the analysis show that partially human relations does not significantly influence the work ethic of the management, while the conditions of the work environment and leadership style significantly influence the work ethic of the management. Together, it shows that human relations, working environment conditions, and leadership style have a significant effect on the management work ethic.Keywords: Human relations, Working Environment Conditions, Work Ethic Leadership Style